Effect of medical treatment on heart failure incidence in patients with a systemic right ventricle. Issue 17 (6th May 2021) - Ladouceur, Magalie; Segura de la Cal, Teresa; Gaye, Bamba; Valentin, Eugenie; Ly, Reaksmei; Iserin, Laurence; Legendre, Antoine; Mousseaux, Elie; Li, Wei; Rafiq, Isma; Kempny, Aleksander; Barradas-Pires, Ana; et al.
Abstract : Background: To date, clinical trials have been underpowered to demonstrate a benefit from ACE inhibitors (ACEis) or angiotensin II receptor blockers (ARBs) in preventing systemic right ventricle (sRV) failure and disease progression in patients with transposition of the great arteries (TGA). This observational study aimed to estimate the effect of ACEi and ARB on heart failure (HF) incidence and mortality in a large population of patients with an sRV. Methods: Data on all patients with an sRV under active follow-up at two tertiary centres between January 2007 and September 2018 were studied. The effect of ACEi and ARB on the incidence of HF and mortality was estimated using a propensity score weighting approach to control confounding. Results: Among the 359 patients with an sRV (32.2 (IQR 26.4–38.3) years, 59.3% male, 66% complete TGA with atrial switch repair and 34% congenitally corrected TGA), 79 (22%) had a moderate to severe sRV dysfunction and 138 (38%) were treated with ACEi or ARB. Fourteen (3.6%) patients died, 8 (2.1%) underwent heart transplantation and 46 (11.8%) had a new HF event over a median follow-up of 7.1 (IQR 4.0–9.4) years. On multivariate Cox analysis with adjustment using propensity score weighting approaches, ACEi or ARBs treatment was not significantly associated with a lower HF incidence or mortality in patients with an sRV. Conclusions: Despite significant neurohormonal activation described in patients with an sRV, there is still no evidence of a beneficial effect of ACEi or ARB on morbidity and mortality in this population.